2015 Glenn A. Fry Award Lecture: Driving toward a New Vision. Issue 9 (September 2019) - Wood, Joanne M.
Abstract : ABSTRACT: More than 90% of the sensory information that we use for driving is estimated to be visual. However, there is ongoing debate regarding the extent to which different ocular conditions and types of visual impairment affect driving performance and which visual functions are most important for safe driving. My program of research has sought to address these questions using a range of experimental approaches including measures of real-world driving performance on a closed-circuit driving course and under in-traffic conditions. This article provides a current overview of how visual impairment affects driving ability and safety and also highlights the visual challenges of nighttime driving, including the visibility of vulnerable road users, based on the wider research literature, as well as providing a snapshot of some of my own studies. Emphasis is placed on those studies that are relevant to assessing a patient's visual fitness to drive, as well as providing appropriate advice regarding the impact of common visual impairments on driving ability and safety. Abstract : Supplemental digital content is available in the text.